PERKEMBANGAN TEKNOLOGI DAN KUALITAS PELAYANAN NASABAH PADA BAITUL MAAL WA TAMWIL LATANSA GONTOR - Annas Syams Rizal Fahmi; Tegar Cahyo Wibowo (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This study aims to determine the effect of technological developments oncustomer service at BMT Latansa Gontor. BMT Latansa Gontor is one of thefinancial institutions that runs its business activities always prioritizing thesatisfaction of its customers, including serving people who want to apply for fundingor save their assets. Various facilities have been offered by BMT Latansa Gontorto make it easier to carry out customer transactions. The services provided byBMT Latansa by following technological developments are not as sophisticatedand as advanced as other Islamic Financial Institutions. But the best service tocustomers is the core of the application of current technological developments.Where most of the Latansa Gontor BMT customers have a background that isnot too middle to upper so that the development of technology and servicesprovided at this time can influence and improve services for Latansan GontorBMT customers. Where the service makes it easier for their affairs and alsoincreases the quality of service to BMT Latansa Gontor customers.